A novel scheme for energy-efficient bridge layer in sensor-cloud - Nasr Musaed Saleh Almurisi; Tadisetty Srinivasulu (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Recently, Sensor-Cloud has been widely utilized in various domains, providing real-time monitoring and remote observations. The sensory data is collected from different heterogeneous WSNs, uploaded to the cloud, virtualized, and served for many user applications. However, the survivability of the physical sensors is a challenge, where the nodes are battery-powered and must be utilized wisely. The need is to extend their lifetime and, thus, ensuring cloud functionality and user satisfaction. In this paper, we address the energy-efficiency of the physical sensors in the Sensor-Cloud paradigm. We propose a new scheme based on layered architecture, in which data transmitted to the cloud through a multi-hop routing. The new scheme introduces a novel algorithm to define a set of nodes called the bridge layer, receiving data from the cluster-head-layer and forwards to the sink node layer. Nodes in the bridge layer are selected according to their final score defined based on their energy-efficiency and distance-efficiency as given by the algorithm. Thus, ensuring a robust layer that helps in reducing the transmission energy and extending overall network lifetime. Our simulation results show an improved performance of our scheme over the scenario without the bridge layer, in terms of several parameters we considered.